Risk Stratification and Recommendations for the cardiovascular disease and metabolic disorder (Research, Society and Development, 2021)
The study sought to describe and analyze the knowledge of professionals about risk stratification and recommendations for cardiovascular diseases and metabolic disorders. The research has a descriptive character with a quantitative approach, carried out with professionals from 11 Primary Health Care Units of regional III, in Fortaleza-CE, November 2020 to January 2021. The sample was listed by 23 nurses and 15 physicians. Data collection took place through a form, through the interaction of professionals via Google Docs. The analysis took place after evaluating the responses to the questionnaire. Data were organized in the database in Excel. There was a high and very high risk for hypertension/diabetes, about 97.4%, totaling 37 professionals reported having knowledge of the stratification of users in the territory they monitor. Approximately (42.1%) of users are stratified as high risk as the majority of the population in their territory, very high risk with 2.6%, which means a stratified user with very high risk. A total of 39.5%, 15 patients at medium risk. As for the source of information on risk stratification for hypertensive/diabetic patients (71.8%) it has it through the family health strategy team, with around 27 participants, 28.9%, 11 professionals have the information through the Management of the unit or by electronic medical record (fastmedic). The implementation of a health care model ensures effective care, providing self-care, adequate professional assistance at the various levels of care in the network, with Primary Care being responsible for coordinating care and organizing the RAS.